FAKTOR-FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION PADA KARYAWAN MATAHARI DI JAKARTA: - Dwi Dwi Prasetya Herman; Netania Emilisa; Farah Jihan Fauzan (Politeknik Ubaya, 2023)
The purpose of this paper is to examine the effect of procedural justice and organizational trust and organizational commitment and turnover intention on a retail company, namely PT Matahahri in Jakarta. Design/methodology/approach – This paper uses a quantitative research design. Data was collected from 120 retail employees of PT Matahari Department store in Jakarta through a questionnaire survey with a list of questions. Structural equation modeling (SEM) was adopted to test the hypothesized model. Findings - Results confirming the positive effect of all the variables concerned or intended on an organization or company intended. The results also confirm that the effect of procedural justice and also organizational trust on organizational commitment and on turnover intention has a positive effect on organizational commitment.